Gridding and interpretation of satellite pictures - SRIDHAR, B. K. (MAUSAM, 1971)
Cloud photographs from the American weather satellites are bein1 received regularly from the middle of May 1966 at the APT Unit, Bombay. Some of the problems faced in gridding and interpretation of these pictures are presented. A few features noticed in these pictures are enumerated.